Synthesis of a New Isoxazolidine and Evaluation Anticancer Activity against MCF-7 Breast Cancer Cell Line - Eneama, Wijdan Abbas; Salman, Husam Hamza; Mousa, Mazin Nadhim (Journal of Science in Medicine and Life, 2024)
In the United States, breast cancer is the most common cancer among women, the second leading cause of cancer-related deaths., and a major contributor to premature mortality as indicated by the average and total number of years of life lost. According to the American Cancer Society, there will be 43,250 fatalities and 287,850 new instances of invasive breast cancer among American women in 2022(1). Heterocyclic compounds containing nitrogen and sulfur constitute over 75% of FDA-approved medications, suggesting the significance of these compounds in the development of drugs(2). of them, heterocyclic compounds containing nitrogen and oxygen, particularly isoxazolidine derivatives, have attracted attention due to their supporting antitumor efficaciousness(3). Several new isoxazolidine derivatives were produced. The MTT assay was used to evaluate for anticancer activity against human cancer cell lines such as MCF-7 and HdFn, as well as normal cells. Structures of Isoxazolidines were defined by FT-IR, 13C-NMR, 1H-NMR, and E-I mass spectroscopy were used to prove the structures of the formed compounds. The IC50 values of the synthesized compounds indicate that compound (IZ2) has a much higher IC50 value in MCF-7 cells than HdFn. Isoxazolidine derivatives bearing a p-Nitro and an m-Nitro aromatic substituent at the isoxazolidine ring showed considerable antitumor activities in Mcf-7 cell lines with IC50 values ranging from 23 µg/ml to 153 µg/ml.